Essential oils from five etlingera species of Sarawak - Nur Anwariah, Marsal (Universiti Malaysia Sarawak, UNIMAS, 2009)
Essential oils from five Etlingera species were studied for their chemical composition and their biological activity on A. salina, Captotermes spp. and three species of fungal (Termetes Versicolor, Gloeophyllum trabeum, Chaetomum globosum). Essential oils were extracted by hydrodistillation method and subsequently analyzed using gas chromatography/flame ionization detector (GC/FID). The percentage of essential oils obtained from the five Etlingera species ranged from 0.11% to 1.83%, with the highest percentage was obtained from the leaf of E. nasuta and the lowest percentage was obtained from the stem of E. kenyalang. The major constituent of E. kenyalang were (E)-p-mentha-2,8-dien-1-ol (43.3%), ethyl isohexanoate (24.5%) and octanal(23.9%). E, nasuta was rich in methyl laurate (26.2%), octanone (26.0%) and (-)-β-bisabolene (24.1%). E. brevilabrum was contain high abundance of mercaptan (20.7%), decane (21.2%) and β-farnesene (11.8%) while E. coccinea has methylfurfurylthiol (27.3%), acetylpyrroline (22.4%) and ethylmethyl pyrazine (18.8%) as the major compounds. Isopulegyl acetate (16.8%), perilla aldehyde (8.8%) and (+)-α-phellandrene (8.3%) were the major components in E. fimbriobractaeta. Essential oils were subjected to three biological activity tests, i.e. brine shrimp, anti-termites and anti-fungal bioassay. No biological activity on A. salina and fungi was observed for all essential oils tested. However, the entire tests carried show that the Captotermes spp. repelled to the smell of the essential oils tested.